Cladotanytarsus Kieffer (Diptera: Chironomidae): several distinctive species reviewed on the basis of records from Canada and USA - Puchalski, Mateusz; Giłka, Wojciech (Zootaxa, 2017)
Two species of the genus Cladotanytarsus Kieffer, 1921 are described as adult males, both peculiar in having distinctively elongated hypopygial anal points. The male of Cladotanytarsus bilyji Giłka et Puchalski, sp. nov. (Canada, Manitoba; USA, Ohio) is presumed to be a close relative of C. nigrovittatus (Goetghebuer, 1922). Another unknown Cladotanytarsus species (USA, Illinois and Louisiana) keys with the European C. donmcbeani Langton et McBean, 2010. The intraspecific variability of the male C. acornutus Jacobsen et Bilyj, 2007 is also presented on the basis of new records (Canada, Ontario; USA, South Carolina). Cladotanytarsus males with similarly structured elongate anal points are reviewed, including C. tobaquardecimus Kikuchi et Sasa, 1990, considered a junior synonym (syn. nov.) of C. conversus (Johannsen, 1932). As a compilation of this study, a key to the identification of the adult males of 14 Cladotanytarsus species is provided.